Mapeamento de fluxo de valor: proposta de construção enxuta para inovação em processos de serviços na construção civil - Pedro, Queli Cunha de Lima (2025)
The construction industry plays a fundamental role in the economic progress of several nations, being one of the main drivers of production and financial movement throughout the production chain. In addition to contributing directly to economic growth, it generates jobs, boosts various sectors of society and promotes tax collection. However, the sector faces significant challenges, such as high consumption of natural resources, waste, resistance to the adoption of innovative technologies, inadequate planning, low productivity and fragmented production flows. In view of this reality, new approaches and management tools have been incorporated, with emphasis on Lean Construction, an innovative methodology that aims to improve the quality and performance of processes, overcoming traditional management methods. The objective of this research was to apply value stream mapping to masonry, internal and external plastering services, to propose improvements and innovations with an action plan based on the principles and tools of Lean Construction, aim at eliminating waste in a multi-family residential project located in Maringá/PR. Through this approach, it was possible to analyze the processes and identify waste during the execution of the services studied. The mapping of the value stream in the current and desired state, together with the proposed action plan, resulted in the elimination of 236.17 minutes of waste, in addition to promoting a reduction of approximately 23.5% in processing time for the masonry lifting service and 17% for the internal and external plastering services.